Using routine blood parameters to anticipate clinical outcomes in invasive aspergillosis. (June 2020) - Pang, L.; Zhao, X.; Dickens, B.L.; Lim, J.T.; Cook, A.R.; Netea, M.G.; Donnelly, J.P.; Herbrecht, R.; Johnson, E.M.; Maertens, J.A.; Kullberg, B.J.; Troke, P.F.; et al.
Abstract: Objective: In invasive aspergillosis (IA), monitoring response to antifungal treatment is challenging. We aimed to explore if routine blood parameters help to anticipate outcomes following IA. Methods: Post hoc secondary analysis of two multicenter randomized trials was performed. The Global Comparative Aspergillosis Study (GCA, n  = 123) and the Combination Antifungal Study (CAS, n  = 251) constituted the discovery and validation cohorts respectively. The outcome measures were response to treatment and survival to 12 weeks. Interval platelet, galactomannan index (GMI) and C-reactive protein (CRP) levels prior and during antifungal treatment were analysed using logistic regression, Kaplan–Meier survival and receiver operating characteristic (ROC) analyses. Results: The 12-week survival was 70.7% and 63.7% for the GCA and CAS cohorts respectively. In the GCA cohort, every 10 × 10 9 /L platelet count increase at week 2 and 4 improved 12-week survival odds by 6–18% (odds ratio (OR) 1.06–1.18, 95% confidence interval (CI) 1.02–1.33). Survival odds also improved 13% with every 10 mg/dL CRP drop at week 1 and 2 (OR 0.87, 95% CI 0.78−0.97). In the CAS cohort, week 2 platelet count was also associated with 12-week survival with 10% improved odds for every 10 × 10 9 /L platelet increase (OR, 1.10, 95% CI 1.04−1.15). A GMI drop of 0.1 unit was additionally found to increase the odds of treatment response by 3% at the baseline of week 0 (OR 0.97, 95% CI 0.95−0.99). Week 2 platelet and CRP levels performed better than GMI on ROC analyses for survival (area under ROC curve 0.76, 0.87 and 0.67 respectively). A baseline platelet count higher than 30 × 10 9 /L clearly identified patients with >75% survival probability. Conclusions: Higher serial platelets were associated with overall survival while GMI trends were linked to IA treatment response. Routine and simple laboratory indices may aid follow-up of response in IA patients.